Just Prayer : A Book of Hours for Peacemakers and Justice Seekers - Benders, Alison M. (Book collections on Project MUSE., 2015)
Just Prayer is a four-week prayer cycle for morning and evening readings to support people who 'hunger and thirst for justice.' Patterned on the ancient monastic Hours, it offers psalms, intercessions, and reflections fashioned to strengthen a personal commitment to justice. The weekly themes are: recognizing God's command that we act justly; lamenting suffering and injustice in our world; repenting our failures and renewing our commitment to justice; and, finally, celebrating God's promise of justice lived as a new heaven and new earth. Weekly reflections encourage personal transformation by emphasizing the connection between justice action and peaceful communities. Created with parishes, youth groups, mission trip participants, and social justice organizations in mind, Just Prayer supports hands-on service work in local communities. By repeating and building upon the prayer sequences in Just Prayer, we can conform our hearts more fully to Christ's living message of compassion and justice for the least among us.